A qualitative study to identify indicators of the quality of wound closure. Issue 5 (September 2019) - Blencowe, NS; Rooshenas, L; Tolkien, Z; Bera, KD; Gould Brown, H; Elliott, D; Reeves, BC; Blazeby, JM
Background: Wound healing after surgery may be complicated by surgical site infection (SSI). SSI development may be influenced by surgical techniques surrounding primary wound closure; for example, the standard to which surgical wounds are closed at the end of an operation. Aim: This study aimed to identify indicators of the quality of wound closure, and factors affecting this, to enable the future development of a tool to measure the quality of wound closure in the context of abdominal surgery. Methods: This study was undertaken within the context of an ongoing feasibility study comparing dressing strategies for patients undergoing abdominal surgery. Content analysis of published literature, non-participant observations of wound closure in the operating theatre, and semi-structured interviews with clinicians were used to identify indicators of the quality of wound closure. Results: A long list ( n  = 38 domains) was categorized into visible markers indicating the quality of wound closure (e.g. suture visibility, apposition of wound edges, evidence of gaps in the wound or tethering of the skin edges), factors that might influence this (e.g. surgeon's expertise, time taken to closure the wounds) and patient factors (e.g. obesity, skin conditions). Conclusions: This is the first study to investigate what is meant by 'good wound closure' and factors that might influence it. Findings will result in the development of a tool to assess quality of primary wound closure.